Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu Hamil Tentang Skrining Hipotiroid Kongenital di PKM Cikuya Kabupaten Tangerang - Hesti Purnama; Wiwin Widyastuti (Universitas Pahlawan Tuanku Tambusai, 2025)
One of the causes of infant mortality due to Congenital Hypothyroidism (CH) is the lack of thyroid hormone production in newborns. This can occur due to anatomical abnormalities of the thyroid gland or iodine deficiency. Government efforts to reduce morbidity and developmental disorders in infants can be done by Congenital Hypothyroidism Screening which can be interpreted as early detection or secondary prevention. The basis of screening is if diagnosis and treatment can be done before signs and symptoms appear so that the prognosis for success will be better than if signs and symptoms have already occurred. The purpose of the study was to determine the Effect of Health Education on Pregnant Women's Knowledge About Congenital Hypothyroidism Screening at PKM Cikuya, Tangerang Regency. The research method was Quasy Experiment with a pre-test-post-test one group design. The research sample was 40 pregnant women selected by Total sampling. Data collection used a knowledge questionnaire of 15 questions. Data analysis used univariate and Wilxocon tests. The results showed that most pregnant women before being given health education had poor knowledge (57.5%) and after the intervention had good knowledge (65.0%). The results of the analysis showed a p-value of 0.001. It is concluded that there is an influence of Health Education on Pregnant Women's Knowledge About Congenital Hypothyroid Screening at PKM Cikuya, Tangerang Regency (p-value = 0.001). Suggestion It is hoped that midwives can develop the SHK program as an implementation of screening carried out on pregnant women early.